SOSIALISASI PERMAINAN TRADISIONAL UNTUK SISWA SD DI SDN 104202 BANDAR SETIA - Ade Evriansyah Lubis; Mhd Fahmi; Mawardinur Mawardinur; Filli Azandi; Agung Nugroho (LPPM Universitas Bina Bangsa, 2021)
Character formation should be done as early as possible. Early age is a time when a person gets the right to play with high intensity. One of the processes of character building can be done in the learning process of formal education. Moreover, the most economical form of a game is the traditional game. Therefore, efforts are needed to actualize traditional game activities for elementary school students. The socialization process was carried out using a demonstration method, both theoretically and practically. Moreover, data collection was carried out using a questionnaire. As for the results of this Community Service activity, it can be concluded that the activity went well where the principal, teachers, and students were very enthusiastic in implementing a series of socialization activities for traditional games.